The Impact of Sustainability on Contractor Selection Criteria in Construction Projects: A Comprehensive Review - mahmoud salim; Khaled Heiza; Ibrahim Mahdi; mohamed saffan (JES: Journal of Engineering Sciences)
This paper investigates the increasing emphasis on sustainable practices within the construction industry and its impact on contractor selection criteria. Recognizing the pivotal role of contractors in project success, this study examines the shift in selection criteria towards incorporating sustainability considerations for both project completion and promoting environmentally responsible construction practices. Through a structured review of literature from documented databases and prominent journals published between 2010 and 2024, this research aims to achieve three primary objectives: first, to delineate and classify conventional criteria employed in contractor selection processes; second, to highlight the emergence of contemporary criteria prioritizing sustainability, particularly in the context of green building projects; and third, to comprehensively analyze the current state of knowledge and identify research gaps concerning the influence of sustainability on contractor selection, utilizing structured review methodologies. The key finding of this research indicates that the contractor selection process is significantly influenced by sustainability considerations. When selecting contractors for green building projects, it is essential to integrate sustainability-related criteria, such as environmental and social factors, along with contractors' qualifications in green construction, into the traditional evaluation framework. This study identified a primary limitation: despite reviewing 70 research papers, it is not possible to definitively claim that all relevant publications on contractor selection were examined. The findings of this study provide valuable insights for future research endeavors aimed at developing comprehensive contractor selection models that integrate sustainable criteria alongside traditional criteria.